2003
DOI: 10.1128/mcb.23.12.4371-4385.2003
|View full text |Cite
|
Sign up to set email alerts
|

Heart and Liver Defects and Reduced Transforming Growth Factor β2 Sensitivity in Transforming Growth Factor β Type III Receptor-Deficient Embryos

Abstract: The type III transforming growth factor ␤ (TGF␤) receptor (T␤RIII) binds both TGF␤ and inhibin with high affinity and modulates the association of these ligands with their signaling receptors. However, the significance of T␤RIII signaling in vivo is not known. In this study, we have sought to determine the role of T␤RIII during development. We identified the predominant expression sites of ⌻␤RIII mRNA as liver and heart during midgestation and have disrupted the murine T␤RIII gene by homologous recombination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
180
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(189 citation statements)
references
References 61 publications
9
180
0
Order By: Relevance
“…Alternatively, it is also formally possible that the high frequency of VSDs in these mutants may be a secondary consequence of cerebral haemorrhage leading to reduced blood flow that might, in turn, affect maturation of the heart. On the other hand, a primary defect caused by reduced TGFb signalling in the heart would be consistent with the increased frequency of VSDs seen in embryos that are non-haemorrhagic, but are deficient in betaglycan, an auxiliary receptor that promotes TGFb2 signalling (Stenvers et al, 2003;Compton et al, 2007). In one of these studies, Betaglycan null embryos died at E14, which was thought to be a result of lack of coronary vessels (Compton et al, 2007).…”
Section: (Asterisk) Efmentioning
confidence: 64%
“…Alternatively, it is also formally possible that the high frequency of VSDs in these mutants may be a secondary consequence of cerebral haemorrhage leading to reduced blood flow that might, in turn, affect maturation of the heart. On the other hand, a primary defect caused by reduced TGFb signalling in the heart would be consistent with the increased frequency of VSDs seen in embryos that are non-haemorrhagic, but are deficient in betaglycan, an auxiliary receptor that promotes TGFb2 signalling (Stenvers et al, 2003;Compton et al, 2007). In one of these studies, Betaglycan null embryos died at E14, which was thought to be a result of lack of coronary vessels (Compton et al, 2007).…”
Section: (Asterisk) Efmentioning
confidence: 64%
“…(Costell et al, 1999) Tenascin C Extracellular matrix Total NC cells fail to disperse laterally (Tucker, 2001) Laminin γ1 Extracellular matrix Total Death at E5.5, lack of basement membranes (Smyth et al, 1999) Laminin β2 Extracellular matrix Total Postnatal death between P15-30, neuromuscular junctions and glomerular defects (Noakes et al, 1995a;Noakes et al, 1995b;Patton et al, 1997) Laminin α2 Extracellular matrix Total Death by 5 weeks postnatal, severe muscular dystrophy and peripheral neurophathy (Miyagoe et al, 1997) Laminin α2 (dy/dy) Extracellular matrix Spontaneous Adult lethality, severe muscular dystrophy and peripheral nerve dysmyelination (Patton et al, 1999;Patton et al, 1997) Laminin α3 Extracellular matrix Total Death at P2-3, epithelial adhesion defect (Ryan et al, 1999) Laminin α4 Extracellular matrix Total Transient microvascular defect with hemorrhages and misalignment of neuromuscular junctions (Patton et al, 2001;Thyboll et al, 2002) Laminin α5 Extracellular matrix Total Death at E14-E17, with placental vessel, neural (Miner et al, 1998;Miner and Li, 2000) Protein Function Type Phenotype Reference tube, limb, and kidney defects Fibronectin Extracellular matrix Total Death before E14.5, shortened anterior-posterior axes, deformed neural tubes, and defects in mesodermally derived tissues. (George et al, 1993) Collagen XVIII Extracellular matrix Total Eye abnormalities modeling Knoblock syndrome (Fukai et al, 2002) Extracellular matrix Total Basement membrane defects (Utriainen et al, 2004) Collagen XV Extracellular matrix Total Skeletal myopathy and cardiovascular defects (Eklund et al, 2001) betaglycan Extracellular matrix Total Embryonic lethality of heart and liver defects (Stenvers et al, 2003) Connexin 43 Cell-cell adhesion In vitro studies of cells from knockout mice…”
Section: Note On Nomenclaturementioning
confidence: 99%
“…Betaglycan-deficient mouse embryo fibroblasts show reduced Smad2 nuclear translocation and reduced growth suppression in response to TGF-b2 stimulation, but not in response to TGF-b1 and TGF-b3 (Stenvers et al 2003). Betaglycan also binds and promotes signaling by inhibin (Lewis et al 2000;Wiater et al 2006) and BMPs (Kirkbride et al 2008;Lee et al 2009).…”
Section: Betaglycan/tbriiimentioning
confidence: 99%
“…Knockout of the betaglycan gene results in embryonic lethality (Stenvers et al 2003); betaglycan has been shown to interact with the scaffolding protein arrestin and thereby activate Cdc42 and inhibit cell migration (Mythreye and Blobe 2009) and to promote neuronal differentiation by interacting with fibroblast growth factor 2 (FGF-2) and FGF receptor 1 (Knelson et al 2013). Betaglycan has also been shown to affect TbRI and TbRII trafficking and signaling (see further below).…”
Section: Betaglycan/tbriiimentioning
confidence: 99%